Palladium-catalyzed carbene/alkyne metathesis with enynones as carbene precursors: synthesis of fused polyheterocycles. Issue 4 (13th December 2017) - Zheng, Yang; Bao, Ming; Yao, Ruwei; Qiu, Lihua; Xu, Xinfang
Abstract : An unprecedented palladium-catalyzed carbene/alkyne metathesis reaction of alkyne-tethered enynones is described, which delivers fused-furans in moderate to good yields. Abstract : An unprecedented palladium-catalyzed novel carbene/alkyne metathesis cascade reaction of alkyne-tethered enynones is described. This reaction affords fused polyheterocycles in moderate to good yields. The transformation begins with Pd-catalyzed 5- exo -dig cyclization of the enynone to form the donor/donor metal carbene, which then undergoes metathesis with the alkyne followed by electrophilic aromatic substitution.